Informed Consent for Newborn Genomic Screening: Interest-Holder Perspectives on Dynamic Consent in an Evolving Landscape - Marina Okamura; Emma Minchin; Carolyn Mazariego; Jolyn Hersch; Natalie Taylor; Ilona Juraskova (International Journal of Neonatal Screening, 2025)
Newborn Bloodspot Screening (NBS) has significantly advanced early disease detection, preventing severe disability and infant mortality. The anticipated integration of genomic technologies into NBS (gNBS) promises earlier diagnosis and targeted treatments. However, it also introduces complexities that necessitate enhanced consent processes. Dynamic Consent Platforms (DCPs), with their layered information and modifiable preferences, may fulfil this rapidly evolving need. This qualitative study explored NBS and genomic interest-holder perspectives on (i) challenges in obtaining informed consent within the current and genomic NBS contexts, and (ii) the acceptability, feasibility, and utility of DCPs for genomics. Sixteen key interest-holders involved in NBS/genomic consent (midwives, genetic counsellors, geneticists, researchers, pathologist, consumer advocate) completed a semi-structured interview. Thematic analysis identified four main themes: (i) looking towards genomic expansions, (ii) systemic issues, (iii) genomic consent information, and (iv) Dynamic Consent Platforms. Participants emphasised revising the timing of consent processes and standardising consent training for clinicians. A nationally standardised DCP was perceived as valuable for addressing consent challenges within gNBS; however, concerns were raised regarding accessibility of online resources for vulnerable populations and integrating DCPs into healthcare systems. Recommendations for future research and clinical implications in this evolving field are discussed.